2010
DOI: 10.1074/jbc.m110.182915
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Macrophage Lipidome

Abstract: We report the lipidomic response of the murine macrophage RAW cell line to Kdo 2 -lipid A, the active component of an inflammatory lipopolysaccharide functioning as a selective TLR4 agonist and compactin, a statin inhibitor of cholesterol biosynthesis. Analyses of lipid molecular species by dynamic quantitative mass spectrometry and concomitant transcriptomic measurements define the lipidome and demonstrate immediate responses in fatty acid metabolism represented by increases in eicosanoid synthesis and delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
286
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(310 citation statements)
references
References 31 publications
20
286
1
3
Order By: Relevance
“…The effects of lipids and inflammatory signaling on ceramide production have been studied in established cell lines, and our data show that these stimuli regulate ceramide production differently in primary macrophages. In cultured RAW 264.7 macrophages, TLR activation has been shown to increase sphingolipid and ceramide content (15,16). As with other cell types, palmitate treatment of RAW cells has also been shown to increase total cellular ceramide (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of lipids and inflammatory signaling on ceramide production have been studied in established cell lines, and our data show that these stimuli regulate ceramide production differently in primary macrophages. In cultured RAW 264.7 macrophages, TLR activation has been shown to increase sphingolipid and ceramide content (15,16). As with other cell types, palmitate treatment of RAW cells has also been shown to increase total cellular ceramide (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytokine production, another consequence of TLR4-mediated macrophage activation is the remodeling of cellular lipids. Recent lipidomic data has revealed that TLR4 activation of RAW 264.7 cells increases total cellular sphingolipids, including ceramides (15,16). These findings are of particular interest because ceramides have been implicated in a wide variety of cell stress responses including cell death, proliferation, inflammation, autophagy, and insulin resistance (17,18).…”
mentioning
confidence: 99%
“…Although the current lipidomic methodologies have succeeded in elucidating the molecular composition of major GP classes, complex GSPs were neglected within common lipidomic routines (14,(23)(24)(25). These lipid classes, however, are both biologically important and abundant (19,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…By combining high mass resolution MS, an improved extraction procedure that increases the recovery of polar lipids (13), and the use of internal standard mixtures for absolute quantification, we expanded the lipid repertoire covered by shotgun lipidomics to glycosphingolipids (GSPs). Importantly, the analysis of the GSPs did not require the hydrolysis of glycerophospholipids (GPs) (14), and this simplification allowed us to determine the membrane lipidome with unprecedented comprehensiveness (more than 300 lipid species from 14 different lipid classes) from a single sample of 10 5 cells.…”
mentioning
confidence: 99%
“…Together, we developed novel liquid chromatographic-mass spectrometric-based lipidomics techniques termed "CLASS" (138) using a quantitative approach based on over 500 LIPID MAPS synthetic standards and specific agonists such as Kdo 2 -Lipid A (154). This approach was applied to the overall omics analysis of some 500 lipid species in immunologically activated macrophages integrating transcriptomics, proteomics, and metabolomics of lipid metabolites (155). Novel methods for separating and assessing the purity of subcellular organelles (156) were developed and employed to determine the subcellular localization of many individual lipid molecular species and their changes during macrophage activation (157).…”
Section: Charting a Course For Lipid Researchmentioning
confidence: 99%